تأثير البرنامج النووي الإيراني على ســــــورية (اقتصادياً) - صيوح, لؤي; سكيف, سامر (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف البحث إلى تحديد تأثير البرنامج النووي الإيراني على الصادرات والواردات. وقد تمّ اعتماد المنهج التاريخي والتحليلي من خلال دراسة تحليل الانحدار الخطي لأثر الزمن على الصادرات والواردات والإنفاق العسكري السوري. وقد قدّم الباحث أهم النتائج التي تم التوصل إليها، والتي منها: يوجد تأثير إيجابي للبرنامج النووي الإيراني على الصادرات والواردات السورية. وقدّم الباحث بعض التوصيات أهمها: المراجعة الدورية والمستمرة لشكل العلاقات الاقتصادية السورية الإيرانية وتعزيز نقاط القوة فيما يخص الصادرات السورية وتحقيق زيادة نوعية في مستوى هذه الصادرات مما ينعكس إيجاباً على الوضع الاقتصادي السوري. The study aimed at determining the impact of the Iranian nuclear program on Syrian exports. The historical and analytical approach was adopted by studying the linear regression analysis of the impact of time on Syrian exports, imports and military spending. The researcher presented the most important results reached, including: there is a positive impact of the Iranian nuclear program on Syrian exports and imports. The researcher made some recommendations, the most important of which is the periodic and continuous review of the Syrian- Iranian economic relations, strengthening, the strengths of Syrian exports and achieving a qualitative increase in the level of these exports, which will positively affect the Syrian economic situation.